UPACARA BHUTA YADNYA SEBAGAI AJANG PELESTARIAN ALAM - M. Yusuf; Ali Mursyid Azisi (UIN Sunan Kalijaga Yogyakarta, 2020)
Human life can not be separated from the natural world around it. Nature is the main source of humans to connect the chain of life. Suber food basically comes from nature which is then processed in such a way by humans. That way, it is very necessary to have actions that are caring and conserving nature so that it is maintained. In Hinduism, there is the term Panca Yadnya which contains the worship or sacrifice which is done sincerely and sincerely from the heart. One of the elements of the five Yadnya is done to the Butha to preserve nature and harmony of human life during the world called the Bhuta Yadnya. In another sense, Bhuta Yadnya is an offering made with the welfare of plants. Of course this is also related to natural conditions which are an important component in supporting the survival of human life. The relationship between nature and humans is inseparable because the two are interrelated, therefore, it is necessary to have a reciprocal relationship in maintaining a balance between the two. In this paper, it explains about the role of the Panca Yadnya ceremony or the five types of sacrifices performed in Hindu beliefs, especially regarding the Bhuta Yad whose role is to preserve nature. In undergoing the life cycle of the world, humans play an important role in preserving the surrounding natural preservation.